The Munāsabāt al-Nuzūl Approach as a Reformulation of Asbāb al-Nuzūl: A Study of Surah al-Fatihah and its Relevance to the Foundations of Islamic Theology - Risma Zuhdiyah Mafaza; Aswadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Studies of asbāb al-nuzūl have been key to understanding the historical context of revelation, but the special position of Surah al-Fātiḥah as the core of Islamic teachings demands an understanding that transcends temporal events. This study aims to offer a new analytical framework through the concept of munāsabāt al-nuzūl to reveal the theological and universal message of the surah. Using a descriptive qualitative method based on library research, this study integrates historical data with an analysis of the correlation between values in the text. The results show that the munāsabāt al-nuzūl approach is able to position al-Fātiḥah as a dynamic and timeless guide for humanity. These findings reveal that al-Fātiḥah comprehensively summarizes the relationship between servants and God through the dimensions of theology, worship, and divine guidance. Thus, this study contributes to the development of a more comprehensive methodology of tafsir science by offering a perspective that not only emphasizes historical factors but also highlights the interconnection of universal values that are contextually timeless for humanity.